Identifying residual foci of Plasmodium falciparum infections for malaria elimination: the urban context of Khartoum, Sudan - Nourein, A; Abass, M; Nugud, A; El Hassan, I; Snow, R; Noor, A (Public Library of Science, 2011)
Background: Identifying the location and size of residual foci of infections is critical where malaria elimination is the primary goal. Here the spatial heterogeneity of Plasmodium falciparum infections within the urban extent of Khartoum state in Sudan is investigated using data from cross-sectional surveys undertaken from 1999 to 2008 to inform the Khartoum Malaria Free Initiative (KMFI). Methods: From 1999-2008 the KMFI undertook cross-sectional surveys of 256 clusters across 203 random samples of residential blocks in the urban Khartoum state in September of each year. Within sampled blocks, at least five persons, including at least one child under the age of five years, were selected from each household. Blood smears were collected from the sampled individuals to examine the presence of P. falciparum parasites. Residential blocks were mapped. Data were analysed for spatial clustering using the Bernoulli model and the significance of clusters were tested using the Kulldorff scan statistic. Results: A total of 128,510 malaria slide examinations were undertaken during the study period. In 1999, overall prevalence was 2.5%, rising to 3.2% in 2000 and consistently staying below 1% in subsequent years. From 2006, over 90% of all surveyed clusters reported no infections. Spatial clustering of infections was present in each year but not statistically significant in the years 2001, 2002, 2004 and 2008. Spatial clusters of high infection were often located at the junction of the Blue and White Niles. Conclusion: Persisting foci of malaria infection in Khartoum are likely to distort wide area assessments and disproportionately affect future transmission within the city limits. Improved investments in surveillance that combines both passive and active case detection linked to a geographic information system and a more detailed analysis of the location and stability of foci should be undertaken to facilitate and track malaria elimination in the state of Khartoum.